PERANCANGAN ANTARMUKA PEMODELAN PERHITUNGAN TERBARUKAN HARGA ENERGI BERBASIS WEB - , GILANG BIMA SAKTI S.P., Widyawan, ST., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Having the knowledge and understanding in renewable energy matters is a must for Indonesian people nowadays. Therefore, a specific service that provides the ability to simulate and calculate certain information for a long-term energy investmen needs to be developed. Another concern is the compatibility of this service to be operated in different devices. The user interface design for each devices must meet the requirements so that any user can experience and access the service in the most user-friendly manner. For this to happen, the concept of human computer interaction (HCI) must be applied. With the help of CSS and Javascript, the most sophisticated web based user interface design can be created. This service will contain some detailed information about each renewable energy, the location of energy distribution in Indonesia, some government regulation related to the energy, the simulator for energy investment calculation, and also there will be a glossary that consists of important words related to renewable energy.